Aplikasi Penilaian Siswa Berbasis Java Pada SMKN 63 Jakarta Selatan - Andri Andri; Sepni Yanti (Peneliti.net, 2021)
In Assessment is the process of collecting and processing information to determine the achievement of student learning outcomes. Currently, the assessment system at SMKN 63 Jakarta is still carried out in a simple computerized way using Microsoft Excel and manual recording, causing various kinds of problems. The problem faced by SMKN 63 Jakarta is the assessment in the student data collection process, subjects, grades are not recorded accurately and well-integrated so that in the search process one has to look for student grade data one by one and is slow in reporting student grades. Lack of security in the system is also a problem at SMKN 63 Jakarta because it can be accessed by anyone. Therefore, to facilitate the work of admin staff, teachers, and homeroom teachers in managing student score data so that it can be completed more quickly, precisely, and efficiently in student assessments, a Java-Based Student Assessment Application was designed at SMKN 63 Jakarta. The research method used in the application of student assessment at SMKN 63 South Jakarta is quantitative. In addition, researchers also researched with data collection methods which included field studies and literature studies. And in developing the system, the researcher uses the waterfall method. And testing the system with the black box testing method. This application is designed using UML (Unified Modeling Language) and using the JAVA programming language with Netbeans IDE, and MYSQL database using XAMPP